Regional variations in the relationship between arterial stiffness and adipocyte volume or number in obese subjects - Arner, P; Bäckdahl, J; Hemmingsson, P; Stenvinkel, P; Eriksson-Hogling, D; Näslund, E; Thorell, A; Andersson, D P; Caidahl, K; Rydén, M (INTERNATIONAL JOURNAL OF OBESITY, 2015)
Background: Cardiovascular disease is associated with multiple risk factors including stiff arteries and large adipocytes. Whether the latter two are interrelated is unknown. We aimed to determine whether arterial stiffness is associated with fat cell size and number in subcutaneous or visceral white adipose tissue (WAT). Methods: A cross-sectional study of 120 obese subjects scheduled for bariatric surgery in whom WAT mass and distribution was assessed by dual-X-ray absorptiometry. Biopsies from visceral (greater omentum) and subcutaneous (abdominal) WAT were obtained to calculate fat cell volume and number. Arterial stiffness was determined as aortic pulse wave velocity (PWV). Results: Visceral adipocyte volume, but not number, was strongly ( P <0.0001) and positively correlated with PWV, explaining 20% of the inter-individual variations in this parameter. This relationship remained significant after correction for clinical confounders. PWV correlated positively ( r =0.38, P <0.0001) with visceral (but not subcutaneous) WAT mass. Furthermore, PWV was also positively associated with subcutaneous adipocyte volume ( r =0.20, P =0.031) and negatively with fat cell number ( r =−0.26, P =0.006). However, the relationships between PWV and visceral WAT mass or subcutaneous fat cell size/number became non-significant when controlling for visceral fat cell volume. In a multiple regression analysis to determine the factors that explain variations in PWV, only visceral fat cell volume, age, pulse rate and diastolic blood pressure entered the model, together explaining 42% of the variation in PWV. Conclusions: Visceral fat cell volume was the only WAT parameter that constituted an independent and significant, positive regressor for arterial stiffness determined by PWV. Although a causal relationship is not established, visceral fat cell volume may explain the well-known correlation between central fat mass, arterial stiffness and cardiovascular risk, at least in severely/morbidly obese subjects.